2009
DOI: 10.1111/j.1349-7006.2009.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein and colorectal adenomas: Self Defense Forces Health Study

Abstract: Chronic inflammation has been implicated in colorectal carcinogenesis. Several studies have investigated the relationship between C-reactive protein (CRP), a biomarker of inflammation, and colorectal cancer and adenomas, resulting in inconsistent findings. The present study examined the relationship between circulating levels of high-sensitivity CRP and colorectal adenomas. The study subjects comprised 646 cases of colorectal adenoma and 635 controls of normal total colonoscopy among men receiving a preretirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…However, the existing literature on this topic is inconsistent. A recent Japanese study reported that CRP levels> 90 th percentile were associated with a >2-fold increase in the odds of large colorectal adenomas(9). A cross-sectional Chinese study also reported that elevated CRP levels were associated with increased risk of advanced adenomas and multiple adenomas(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existing literature on this topic is inconsistent. A recent Japanese study reported that CRP levels> 90 th percentile were associated with a >2-fold increase in the odds of large colorectal adenomas(9). A cross-sectional Chinese study also reported that elevated CRP levels were associated with increased risk of advanced adenomas and multiple adenomas(10).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported that CRP is associated with higher risk of colorectal adenomas (9, 10), others have found null (11-13), or even inverse associations(14). To our knowledge, no study has previously examined the association between inflammatory markers and serrated polyps (SPs), yet some of these lesions are now understood to be important CRC precursors as well.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies were nested case-control studies, 9 had a case-control design, and one was cross-sectional. The studies were conducted in the United States[10,11,13,16,18,19,21-23], Japan[12,14,15,17], and the United Kingdom[20]. Four studies investigated advanced and 4 studies non-advanced adenoma.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies investigated advanced and 4 studies non-advanced adenoma. Measurements methods varied greatly between studies, including INA (Immunonephelometric Assay)[12,14,19,20], ITA (Immunoturbidimetric Assay)[13,21,23], ELISA[10,13,17,18,23], DADE-Behring method[11], Chemiluminescent Immunometric Assay[16], Cytometric Bead Array[20], Cytokine/Chemokine Magnetic Bead Panel Assay[15,18,22]. Seven studies tested markers of inflammation in plasma, 5 in serum, and 2 in serum and plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation